2018
DOI: 10.1186/s12940-018-0368-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the endocrine activity of air pollutants associated with unconventional oil and gas extraction

Abstract: BackgroundIn the last decade unconventional oil and gas (UOG) extraction has rapidly proliferated throughout the United States (US) and the world. This occurred largely because of the development of directional drilling and hydraulic fracturing which allows access to fossil fuels from geologic formations that were previously not cost effective to pursue. This process is known to use greater than 1,000 chemicals such as solvents, surfactants, detergents, and biocides. In addition, a complex mixture of chemicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 138 publications
2
16
0
3
Order By: Relevance
“…Multiple studies have identified several VOCs in the air near OG operations in Colorado [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Some of these VOCs are categorized as hazardous air pollutants by the U.S. EPA and Colorado Regulation 3 (5 CCR 1001-5) due to their potential to cause adverse health effects, such as cancer, neurological, developmental and reproductive effects and some have the capacity to alter endocrine activity at some exposure level [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have identified several VOCs in the air near OG operations in Colorado [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Some of these VOCs are categorized as hazardous air pollutants by the U.S. EPA and Colorado Regulation 3 (5 CCR 1001-5) due to their potential to cause adverse health effects, such as cancer, neurological, developmental and reproductive effects and some have the capacity to alter endocrine activity at some exposure level [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, their association with male genital malformations has been rarely investigated. Although Bolden et al suggested that BTEX-S may have endocrine disrupting properties at exposure levels below reference concentrations, the evidence is scarce (12,52,53). However, an experimental study in rats showed that styrene, one of the principal sources of PGA, has estrogenic properties that can affect genital development of the offspring, such as shortened anogenital distance, lower testis weight, and disruption of hormonal levels (41).…”
Section: Discussionmentioning
confidence: 99%
“…Associations between PM2.5 exposure and neurological disorders have been found in systematic reviews and meta-analyses [83][84][85]. Particular pollutants such as endocrine disruptors and other chemicals used and liberated in shale oil and gas present a range of air borne and water contamination hazards with risks that have not yet been fully quantified [86]. In such settings, the application of the precautionary principle would seem wise [87] and would help reflect ethical and environmental justice concerns in policy development.…”
Section: Situating the Science On Air Pollution And Shale Explorationmentioning
confidence: 99%